2022
DOI: 10.1111/dth.15403
|View full text |Cite
|
Sign up to set email alerts
|

A multi center real world observation to evaluate the efficacy of cryotherapy versus local hyperthermia for the treatment of plane warts

Abstract: Most plane warts are recalcitrant to treatment. Both cryotherapy and local hyperthermia have been applied to treat plane warts. However, no direct comparative study on their respective efficacy and safety has ever been performed. To assess the efficacy and safety of local hyperthermia at 43 ± 1°C versus liquid nitrogen cryotherapy for plane warts. Sequential patients with plane warts entered the study, either receiving cryotherapy or local hyperthermia therapy at the discretion of the patients and the recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In treating multiple HPV-associated warts, when one targeted wart was radiated, warts in the rest of the untreated area would also shed. 6 A study compared the efficacy and safety of local hyperthermia at 43 ± 1°C versus liquid nitrogen cryotherapy for plane warts during 6 months, and the results suggested that although local hyperthermia and cryotherapy achieved similar clearance rates, local hyperthermia had the lower recurrence and adverse events rates, and was preferred by more patients due to its treatment-friendly nature. 7 Similar results were also reported by Izadi et al, 8 they demonstrated that the clearance rate was 79.2% in the thermotherapy group, which is higher than 58.3% in the cryotherapy group; besides, the rate of scarring in the thermotherapy group was also lower.…”
Section: Discussionmentioning
confidence: 99%
“…In treating multiple HPV-associated warts, when one targeted wart was radiated, warts in the rest of the untreated area would also shed. 6 A study compared the efficacy and safety of local hyperthermia at 43 ± 1°C versus liquid nitrogen cryotherapy for plane warts during 6 months, and the results suggested that although local hyperthermia and cryotherapy achieved similar clearance rates, local hyperthermia had the lower recurrence and adverse events rates, and was preferred by more patients due to its treatment-friendly nature. 7 Similar results were also reported by Izadi et al, 8 they demonstrated that the clearance rate was 79.2% in the thermotherapy group, which is higher than 58.3% in the cryotherapy group; besides, the rate of scarring in the thermotherapy group was also lower.…”
Section: Discussionmentioning
confidence: 99%
“…When the irradiation wart subsided, this treatment was close to success. In addition, some studies have shown that local hyperthermia has a higher clearance rate for warts and a lower recurrence rate than cryotherapy, 8 which is particularly suitable for treating PW in children and pregnant women.…”
Section: Discussionmentioning
confidence: 99%